Manufacturing a multifunctional countryside - Bivar, V (Berghahn Books, 2018)
Rural France was instrumental to the experience of les trente glorieuses. Not only did rural France fuel economic growth and urbanization through increases in agricultural efficiency, but it also served as an imaginary counterpoint to the hustle and bustle of a new mass consumer society. In the first two decades of the postwar period, a productivist logic of agricultural output dominated rural land use policy. By the 1970s, however, after experiencing problems of surplus, the state turned toward a multifunctional approach. Rural lands were used to create regional parks, environmental preserves, and vacation properties. As both a site of agricultural production and urban consumption, rural France was operationalized to further the economic growth that defined les trente glorieuses.